Analysis of Environmental Conditions Around Nickel Mining PT. X in Village X Tinanggea District South Konawe Regency - Rauf, Rahman; Azizi Jayadipraja, Erwin; Yulianti Abubaeda, Dewi; Hapsari Hadju, Riny (Waluya The International Science of Health Journal, 2022)
Introduction: Mining activities carried out by PT. X is very detrimental to the environment of residents in Village X. Due to the activities of the nickel mining company, people's rice fields in several villages in Tinanggea District, especially Village X are polluted with mud so that rice growth is hampered and often fails harvest. Method: This type of research is descriptive and quantitative. Samples data was 30 people in X Village Tinanggea District. The data that has been collected in the study were analyzed descriptively. Result: The results of this study are community knowledge that mining activities are a response to community responses, namely (93.3%), community knowledge that activities that arise from these responses are informants (93.3%) and Nickel mining in Village X does not cause health problems with a response in the form of (56.7%). Conclusion: Nickel mining activities have positive impacts, such as: increasing ROI from the mining sector, creating job opportunities, and opening up areas from isolation. Nickel mining activities have a negative impact. Such as the occurrence of environmental damage, like river water becoming blurry and colored and dirty,air pollution, and changes in community behavior.